Media access and reliability for forest conservation support communication in Anambra State, Southeastern Nigeria (2013)
The need for conservation of forests resources, which are presently under continuous depletion, is topical to sustainable development in Nigeria. Despite this, the annual rate of forest depletion in Anambra State is alarming. One of the adduced reasons for this had been inadequate access of residents who rely on forest resources for their livelihood to environmental amelioration information. This study therefore reports the media in use or that could be employed to effectively keep Anambra State residents’ abreast on environmental amelioration issues. The study employed multistage stratified random sampling technique where the state was stratified into three senatorial districts. One local government area with urban, peri-urban and rural settlements were then purposively selected in each district to account for the socio economic background of the people in the study area. Two wards each were picked from each settlement and thirty questionnaires were administered in each ward, giving a total of 540 respondents for the study. Data generated were analysed using descriptive (Tables, frequency counts, percentages and pie chart) and inferential (Pearson’s correlation coefficient, Chi-square and one way Analysis of variance) test statistics at p = 0.05. The study revealed that more people (40.9%) had access to radio followed by television (24.5%) and radio was favored as the most appropriate and reliable medium for dissemination of forest conservation information (FCI) in the study area. Further, majority of respondents listened to radio and television programs in the evening (57.7%). However majority (63.3%) of the respondents could not compare extension agents and mass media messages because they do not have access to extension agents. The study also observed a significant difference in the effectiveness of the different modes of receiving information in the three senatorial districts and a strong positive relationship between the information sources in the study area and access of the sources to the people for FCI. Also, even though a strong positive relationship existed between the respondents’ access to media and the reliability of the media for FCI in Anambra North (r = 0.92), Central (r = 0.86) and South (r = 0.91) senatorial districts, the reliability of media for FCI does not have a relationship with respondents’ access to media among in Anambra North, (χ2 = 59.13), Central (χ2 = 88.0) and South (χ2 = 60.5). In general, environmental outreach goals in the study area will continue to rely on effective communication to the local people who share their rural frontier with the earth’s biological wealth.